Kolaborasi Peran Guru dan Orang Tua dalam Penerapan Disiplin Positif (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2025)
Education can take place at home, school or in the community environment which is known as the three centers of education. The educational trilogy expressed by Ki Hajar Dewantara is: "education in the family environment, education in the school environment, and education in the community environment". Therefore, the education process can take place starting from the family and school, good collaboration is needed between parents and educators in supervising and directing students. Especially in an effort to realize positive discipline for students. This is needed so that there is harmony between parents and educators, so that students can raise an attitude of awareness in themselves towards a disciplined attitude. The method used in this study uses the library method, with the aim of exploring the ideal concept in implementing a positive discipline pattern for students, as well as a guideline for parents and educators to have a foundation in their efforts to implement it. Parents and educators need to know what roles each parent and educator must take in the environment they are under. In addition, cooperative communication is needed between the two so that supervision occurs continuously.